On Kataloglama Kuralları (Cataloging Rules) (Part II) - Necmeddin Sefercioğlu (Türk Kütüphaneciliği)
This paper is a rejoinder to Dr. Hasan S. Keseroğlu s article ["On the Critique of Kataloglama Kuralları (Cataloging Rules)"] that appeared in Türk Kütüphaneciliği [9(2):149-168, June 1995]. Dr. Keseroğlu's article it self was a rejoinder to the present author's critique of his monograph on AACR2, which also appeared in Türk Kütüphaneciliği [8(4):288-303, Fall 1994].